Kedudukan Otorita Ibu Kota Nusantara Dalam Ketatanegaraan Indonesia - Al-Hamid, Syarif Anwar Said; Firmansyah, Ade Arif; Khoiriah, Siti (UI Scholars Hub, 2023)
Otorita of the capital city of the nusantara is a state institution formed by Law Number 3 of 2022 concerning the State Capital which is then regulated in more detail through Presidential Regulation Number 62 of 2022 concerning Otorita of the capital city of the nusantara which becomes a special regional government for the national capital in implementing the development of the capital city archipelago. Head of otorita the capital city of the nusantara is the head of the regional government specifically for the national capital who is elected, appointed and dismissed by the president with the approval of the DPR. This research is to find out about how the position of the government authority agency for the capital city of the nusantara is based on the Indonesian constitutional system. This type of research is to use normative legal research by using a statutory problem approach, historical approach, and conceptual approach. The conclusion from the results of this study is that the authority for the capital city of the nusantara is not a regional government because, based on function and authority, the Otorita of the capital city of the nusantara is included in the auxiliary state's organ which supports the process of moving the national capital formed based on statutory regulations.